THE IMPACT OF WORKING EXPERIENCE AND GENDER TOWARDS AUDIT JUDGMENT WITH PROFESSIONAL SKEPTICISM AS A MODERATING VARIABLE (Empirical Study at BPK RI Jakarta) - Atiwina Katon, Rucira Karayita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Â ABSTRACTWhen the auditors do their duties in order to make professional judgment, they are influenced by many factors. Individual behavior aspect is one of the factors that can impact the making of auditorâ€™s judgment. This study was aimed to prove empirically the professional skepticism as a moderating variable in the influence of auditor experience and gender towards audit judgment. Moreover, the impact of auditor experience and gender on audit judgment were also assessed. This study was conducted at BPK RI headquarter in Jakarta. The sample was chosen by using purposive sampling method. Further, 93 auditors were the number of samples that had been taken. Questionnaires were used as a data collection method. In addition, the analysis technique of this study was moderated regression analysis. After the test and analysis had been taken, the result indicated that working experience significantly influenced the auditorsâ€™ judgment and professional skepticism attenuated the relationship between working experience and audit judgment. Contrarily, gender did not significantly affect the audit judgment as well as professional skepticism did not impact the correlation between gender and auditor judgment.KÐµywords: Working Experience, Gender, Professional Skepticism, Audit JudgmentÂ ÐBSTRÐKKetika auditor melakukan tugasnya untuk membuat penilaian profesional, mereka dipengaruhi oleh banyak faktor. Aspek perilaku individu adalah salah satu faktor yang dapat mempengaruhi pembuatan penilaian auditor. Penelitian ini bertujuan untuk membuktikan secara empiris skeptisisme profesional sebagai variabel moderat dalam pengaruh pengalaman auditor dan jenis kelamin terhadap penilaian audit. Selain itu, dampak pengalaman auditor dan gender pada penilaian audit juga dinilai. Penelitian ini dilakukan di kantor pusat BPK RI di Jakarta. Sampel dipilih dengan menggunakan metode purposive sampling. Jumlah sampel yang telah diambil sebanyak 93 auditor. Metode pengumpulan data menggunakan kuesioner. Selain itu, teknik analisis penelitian ini adalah analisis regresi moderasi. Setelah pengujian dan analisis dilakukan, hasilnya menunjukkan bahwa pengalaman kerja secara signifikan mempengaruhi penilaian auditor dan skeptisisme profesional melemahkan hubungan antara pengalaman kerja dan penilaian audit. Sebaliknya, gender tidak mempengaruhi penilaian audit secara signifikan dan skeptisisme profesional tidak memengaruhi korelasi antara gender dan penilaian auditor.KÐ°tÐ° Kunci: Pengalaman Kerja, Gender, Profesional Skeptisisme, Penilaian AuditÂ